2009
DOI: 10.1002/ca.20907
|View full text |Cite
|
Sign up to set email alerts
|

Imaging study of the long extracranial extension of the inferior petrosal sinus with MSCT

Abstract: The aim of this study was to explore the anatomic route of Long-Inferior Petrosal Sinuses (IPS) with multi-slice spiral computed tomography, and to provide referenced evidence for the interventional preoperative evaluation for the diagnosis and treatment of skull base and sellar lesions. The route of Long-IPS and its confluence with the internal jugular vein (IJV) and the connection level of 12 IPS were shown with multi-planar reconstruction and curved multi-planar reconstruction, and the IPS length was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…These authors further explored the anatomic route of accessory IJV and to provide referenced evidence for the interventional preoperative evaluation for the diagnosis and treatment of skull base and sellar lesions ( Table 7). 21 The length of the IPS was greater than 40 mm in 4.3%. This study showed that the confluence of the accessory IJV with the IJV occurred at from C2-C5 vertebrae, suggesting that the IPS can be searched for at lower levels if a catheter is unable to enter the IPS in the JF.…”
Section: Type IVmentioning
confidence: 91%
“…These authors further explored the anatomic route of accessory IJV and to provide referenced evidence for the interventional preoperative evaluation for the diagnosis and treatment of skull base and sellar lesions ( Table 7). 21 The length of the IPS was greater than 40 mm in 4.3%. This study showed that the confluence of the accessory IJV with the IJV occurred at from C2-C5 vertebrae, suggesting that the IPS can be searched for at lower levels if a catheter is unable to enter the IPS in the JF.…”
Section: Type IVmentioning
confidence: 91%